An audit of diabetic care provided to patients conducted by a doctor-nurse team in a general practice - Navsa, Desiree Miriam (Department of Public Health and Family Medicine, 2017)
Introduction: I am a general practitioner in solo practice in Athlone. I work closely with a qualified nursing sister. Many of the patients we attend to have non-insulin dependent diabetes mellitus. Aim: To implement change in the management of our patients with diabetes by developing a protocol for future improved care. Objective: To assess the quality of care provided to patients with (NIDDM), by a doctor - nurse team in private general practice. Method : The study was quantitative and qualitative and consisted of 3 sections : 1) an internal audit based on the retrospective examination of patients' medical records, 2) a questionnaire which was administered to determine patients' knowledge of their disease and 3) a focus group interview which centred around patients' experience of the disease and feelings about the service provided. The interview was audio taped. Findings: Problem areas identified were sub-optimal record keeping; poor attendance and infrequent eye and foot examinations; patients' knowledge of their disease was limited; certain aspects of doctor-patient and patient-family relationships that may impact negatively on care; fears and anxieties relating to the disease and perceptions oflocus of control as external.